Priapism in Patients Chronic Myeloid Leukemia - Azhari Gani; Muhammad Jailani (Budapest International Research in Exact Sciences (BirEx) Journal, 2020)
The aims of this study are to find out the healing process of Priapism in Patients Chronic Myeloid Leukemia. This study used one case of patient which has some complaint, The patients is man with age 29 years old, The patient complained of an enlarged left stomach since 4 months and became heavy in the last 2 weeks, On vital sign examination, compos mentis awareness was found with blood pressure 110/70 mmHg, pulse 80 times per minute, respiratory rate 20 times per minute and temperature 37oC. On the visual analogue scale (VAS) examination showed a value of 4-6 (moderate pain). The result shows that CML is a hematological malignancy characterized by the Philadelphia chromosome and detected clonal expansion of hematopoietic stem cells from ABL BCR examination on chromosomes 9 and 22 which is characterized by an increase in the number of leukocytes with or without enlargement of the spleen. One of the complications of CML is priapism which occurs due to hyperleukocytosis which causes an increase in the viscosity of the blood and this is a major cause of complications of vascular obstruction. Priapism in CML is classified as low-flow (static / ischemic) caused by venocclusiveness which must be treated immediately to restore blood flow to the cavernous corpora by means of needle aspiration.